2018
DOI: 10.4103/ija.ija_605_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of addition of dexamethasone to ropivacaine on post-operative analgesia in ultrasonography-guided transversus abdominis plane block for inguinal hernia repair: A prospective, double-blind, randomised controlled trial

Abstract: Background and Aims:Ultrasonography (USG)-guided transversus abdominis plane (TAP) block is an abdominal field block with high efficacy. This study was undertaken with the aim of determining the effect of the addition of dexamethasone to 0.5% ropivacaine on post-operative analgesia in USG-guided TAP block for inguinal hernia repair.Methods:A double-blind randomised control study was conducted on sixty patients posted for inguinal hernia repair with the American Society of Anesthesiologists physical Status I or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 22 publications
6
19
0
Order By: Relevance
“…have reported that the addition of dexamethasone to ropivacaine in ultrasonography (USG)-guided TAP block prolongs postoperative analgesia and reduces analgesic consumption. [ 16 ] Metwally et al . have reported that the addition of fentanyl to the local anesthetic in USG-guided TAP block prolongs the analgesia, lowers postoperative pain score and reduces the opioid consumption.…”
Section: Discussionmentioning
confidence: 99%
“…have reported that the addition of dexamethasone to ropivacaine in ultrasonography (USG)-guided TAP block prolongs postoperative analgesia and reduces analgesic consumption. [ 16 ] Metwally et al . have reported that the addition of fentanyl to the local anesthetic in USG-guided TAP block prolongs the analgesia, lowers postoperative pain score and reduces the opioid consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Since the above studies were done under subarachnoid block, early postoperative pain assessment could be misleading. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…There were also variations in the pain scores with the dose of local anesthetics and dexamethasone used in the previous studies. [ 11 12 13 14 15 ] Whether the difference in the onset of analgesia was due to increased local anesthetic concentration or dexamethasone was not evident. Moreover, for surgeries done under subarachnoid block, the early pain score assessment could also be misleading.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations